Experimental Study of the Effect of Wire Electrical Discharge Machining on Crack tip Opening Displacement for Compact Tension Specimens of Low Carbon Steel - Khudair, Sara A.; Taha, Atheed H.; Nassar, Ameen A. (Basrah Journal for Engineering Sciences, 2023)
Fracture mechanics approach is important for all mechanical and civil projects that might involve cracks in metallic materials the purpose of this paper is to determine a crack tip opening displacement fracture toughness experimentally, also study the effect of thickness on CTOD fracture toughness of low carbon steel and study the effect of Wire Electrical Discharge Machine (WEDM) to have a pre-crack, instead of fatigue pre-crack by using a CT specimen of low carbon steel with a thickness of (8,10, and15 mm), a width of 30mm, crack length of 15mm, and pre-crack of 1.3mm for all samples, this dimension according to ASTM-E399-13, by pulling the specimen in a 100 KN universal testing machine at a slow speed rate of 0.5 mm/min, the load applied on the specimen is generally a tension load. The crack tip plastically deforms until a critical point P C at this moment a crack is initiated. The computer-controlled universal testing machine gives the value of the load and the displacement transducer gives a crack mouth opening displacement. Critical crack tip opening displacement CTOD is found with the plastic hinge model (PHM) method. The result showed the stress intensity factor K I increases with increased loading in the elastic region and t he thickness effect refers to the effect of the plastic zone at the crack tip on the stress intensity factor, In a thin specimen, a plastic zone is large at the fracture tip leads to a high-stress intensity factor at the fracture tip but in the thick specimen, on the other hand, has a small a plastic zone and a low-stress intensity factor around the crack tip. The fracture toughness is found to increase with an increase in the thickness of specimens.